Advances of the gender approach in rural productive programs: An approach to the Peruvian case - García de Mercado, Ruth Mercedes (2021)
In light of the interpretive paradigm and the “human development’s theories”, the purpose of this article is to expose some advances in the gender approach in rural productive projects, the potential of this approach in the respective results, and the role of public or private institutions in incorporating this perspective. Through a qualitative methodology of documentary analysis, it’s identified that advances in policies, research and in the formulation of strategies or proposals, that include this perspective are important, confirming the persistence of gender inequalities and incompatibilities between the productive and reproductive roles of women. However, the prospects for enhancing the participation of women in rural productive activities are promising, due to the positive results in several cases. It is also highlighted that institutions play a transcendental role in the advances found, although with limitations.